High-resolution spectroscopic follow-up of the most metal-poor candidates from SkyMapper DR1.1. Issue 3 (15th July 2021) - Yong, D; Da Costa, G S; Bessell, M S; Chiti, A; Frebel, A; Gao, X; Lind, K; Mackey, A D; Marino, A F; Murphy, S J; Nordlander, T; Asplund, M; et al.
ABSTRACT: We present chemical abundances for 21 elements (from Li to Eu) in 150 metal-poor Galactic stars spanning −4.1 < [Fe/H] < −2.1. The targets were selected from the SkyMapper survey and include 90 objects with [Fe/H] ≤ −3 of which some 15 have [Fe/H] ≤ −3.5. When combining the sample with our previous studies, we find that the metallicity distribution function has a power-law slope of Δ(log N)/Δ[Fe/H] = 1.51 ± 0.01 dex per dex over the range −4 ≤ [Fe/H] ≤ −3. With only seven carbon-enhanced metal-poor stars in the sample, we again find that the selection of metal-poor stars based on SkyMapper filters is biased against highly carbon-rich stars for [Fe/H] > −3.5. Of the 20 objects for which we could measure nitrogen, 11 are nitrogen-enhanced metal-poor (NEMP) stars. Within our sample, the high NEMP fraction (55 per cent ± 21 per cent) is compatible with the upper range of predicted values (between 12 per cent and 35 per cent). The chemical abundance ratios [X/Fe] versus [Fe/H] exhibit similar trends to previous studies of metal-poor stars and Galactic chemical evolution models. We report the discovery of nine new r-I stars, four new r-II stars, one of which is the most metal-poor known, nine low-α stars with [α/Fe] ≤ 0.15 as well as one unusual star with [Zn/Fe] = +1.4 and [Sr/Fe] = +1.2 but with normal [Ba/Fe]. Finally, we combine our sample with literature data to provide the most extensive view of the early chemical enrichment of the Milky Way Galaxy.